Identifying the potential of mobile application for e-MUET: a case study / Mashanum Osman, Sazalinsyah Razali, Norhafizah Zaki and Nursyafizila Azizan - Osman, Mashanum; Razali, Sazalinsyah; Zaki, Norhafizah; Azizan, Nurstyafizila (UiTM Press, 2017)
This paper describes a study that has been carried out to examine the effect and use of the mobile application for Malaysian University English Test (MUET). The application is designed for mobile devices that include and mimics the real MUET with the aim to awaken interest and flexibility for the candidates to learn.Two of the main objectives of this study are to develop a mobile application (eMUET) for candidates to facilitate learning and to provide flexibility to learn. The second objective is to evaluate the effects of using eMuet in the learning process. The study uses the quasi experimental approach in order to gather data and obtain feedback from a sample of several groups of undergraduate students in a public Malaysian university. The instruments covered in this paper are disseminating pre and post questionnaires and using the application (eMuet). The study concludes that the use of mobile phones with suitable learning activities is favoured, and it helps improve the participants’ learning experience.